2021
DOI: 10.1111/bjhp.12516
|View full text |Cite
|
Sign up to set email alerts
|

Social‐cognitive predictors of parental supervised toothbrushing: An application of the health action process approach

Abstract: Background. We examined the social cognition determinants of parental supervised toothbrushing guided by the health action process approach (HAPA). Methods.In a prospective correlational survey study, participants (N = 185, 84.3% women) completed HAPA social cognition constructs at an initial time point (T1), and 12 weeks later (T2) self-reported on their parental supervised toothbrushing behaviour, toothbrushing habit, and action control.Results. Structural equation models exhibited adequate fit with the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Empirical research has repeatedly shown good applicability of the HAPA for various health behaviors (e.g., physical activity, dietary behavior, toothbrushing; Schwarzer, 2008; Smith et al, 2021). Within the motivational phase, outcome expectancies and self-efficacy seem to be the most consistent predictors of intention, shown at both the between- and within-person level, whereas risk awareness provides mixed results and might only play a minor role in the process of behavior change (Bierbauer et al, 2017).…”
mentioning
confidence: 99%
“…Empirical research has repeatedly shown good applicability of the HAPA for various health behaviors (e.g., physical activity, dietary behavior, toothbrushing; Schwarzer, 2008; Smith et al, 2021). Within the motivational phase, outcome expectancies and self-efficacy seem to be the most consistent predictors of intention, shown at both the between- and within-person level, whereas risk awareness provides mixed results and might only play a minor role in the process of behavior change (Bierbauer et al, 2017).…”
mentioning
confidence: 99%
“…These findings, along with recent meta‐analytic evidence (Hamilton et al, 2020), indicate that self‐regulatory skills may be necessary for equipping parents with the means to overcome barriers that interfere with their ability to follow‐through on their intentions to perform regular parental supervised toothbrushing. In recent studies (Hamilton et al, 2018; Hariyani et al, 2020; Smith et al, 2020, 2021), the importance of theory‐based interventions to enhance parental involvement in promoting their young children's oral hygiene behaviour has been emphasised. Furthermore, a recent systematic review examining home‐based toothbrushing interventions for parents of young children noted a significant absence of theoretical foundations among the interventions included in the review (Aliakbari et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to establish and pass on regular toothbrushing habits from parent to child during the preschool years to prevent the onset of early childhood caries before the eruption of permanent dentition. Parents generally report high levels of motivation to act in the best interests of their children's health and safety, including their oral health (Hagger, Keech, & Hamilton, 2020;Smith et al, 2021;Spinks & Hamilton, 2015). However, research has well documented that intentions do not reliably predict behaviour, and people often fail to act upon even their best intentions (Hagger & Chatzisarantis, 2009;McEachan et al, 2011;Sheeran & Webb, 2016;C.-Q.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent intervention study showed that college students exhibited reduced sedentary intention and behaviors after they received the action and coping planning intervention (Dillon et al, 2021 ). It is suggested that both action and coping planning can promote health-related behaviors by enhancing behavioral intention (Smith et al, 2021 ). In other words, the two factors are regarded as two different but complementary constructs, conducive to the translation of exercise intention into action (Carraro and Gaudreau, 2013 ; Pinidiyapathirage et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent intervention study showed that college students exhibited reduced sedentary intention and behaviors after they received the action and coping planning intervention (Dillon et al, 2021). It is suggested that both action and coping planning can promote health-related behaviors by enhancing behavioral intention (Smith et al, 2021).…”
Section: Introductionmentioning
confidence: 99%